Web 2.0, dilemmas 1.0: essay on an evolving market - Kerr, Macaulay Duff (2007)
Today the Internet is entwined into our everyday society. From the beginning days in 1980 to today, the Internet has been evolving. The creator of the World Wide Web, Tim Berners-Lee, envisioned that the Internet would be a system with everything connected to everything. The web today is changing with new applications arriving from outside the previous channels of the megalithic software companies. Thousands of individual developers are creating micro-applications to enhance the earlier framework of the web. This revolution has been coined 'Web 2.0'. Many observers today are skeptical that Web 2.0 is really a revolution at all, but maybe is just a continuation of Berners-Lee's original concept. This paper examines, based on a critical literature review, the discussions taking place regarding Web 2.0.